Improvement of the Transient Stability of a 14-bus Network Using a Superconducting Fault-Current Limiter SFCL - S. Belkhiri; M. Bouroubi; A. Harrabi (Advanced Electromagnetics, 2020)
This study presents a new strategy for implementing the superconducting fault current limiter SFCL in order not only to limit short - circuit currents but also to improve the stability of electrical networks in the presence of faults. The calculation of the impedance that the limiter must introduce into the test network at the moment of the failure is obtained from a three-dimensional computation code, developed and implemented under MATLAB environment where the formulation in magnetic vector potentials A and scalar potential Electric V is adopted to solve the electromagnetic problem and the heat diffusion formulation is adopted also to solve the thermal problem. The coupling is ensured by an alternating algorithm and the numerical resolution of the problem is ensured by the method of the finite volumes in its three-dimensional version in order to avoid certain problems of numerical convergence linked to the strongly nonlinear character of the problem to be solved. The modeling of the network tests will be made by PSAT under the environment MATLAB.